PD‐1/PD‐L1 immune checkpoint: Potential target for cancer therapy - Dermani, Fatemeh K.; Samadi, Pouria; Rahmani, Golebagh; Kohlan, Alisa K.; Najafi, Rezvan (Journal of cellular physiology, 2019)
Recent studies show that cancer cells are sometimes able to evade the host immunity in the tumor microenvironment. Cancer cells can express high levels of immune inhibitory signaling proteins. One of the most critical checkpoint pathways in this system is a tumor‐induced immune suppression (immune checkpoint) mediated by the programmed cell death protein 1 (PD‐1) and its ligand, programmed death ligand 1 (PD‐L1). PD‐1 is highly expressed by activated T cells, B cells, dendritic cells, and natural killer cells, whereas PD‐L1 is expressed on several types of tumor cells. Many studies have shown that blocking the interaction between PD‐1 and PD‐L1 enhances the T‐cell response and mediates antitumor activity. In this review, we highlight a brief overview of the molecular and biochemical events that are regulated by the PD‐1 and PD‐L1 interaction in various cancers. In this review, we highlight a brief overview of the molecular and biochemical events that are regulated by the PD‐1 and PD‐L1 interaction in various cancers.